Trwałe leśnictwo w czasach zdominowanych przez sektor finansowy - Köpf, Ernst (Leśne Prace Badawcze, 2012)
Sustainability has been a guiding principle of forestry in Europe for the last two hundred years, but at present the principle of sustainability is challenged by global economic pressures, ‘limits to growth’ are unavoidable in the global civilization, but this does not mean that nothing should grow! Money permits us to use markets to differentiate production and to exchange goods and services. Forestry firms, like all others, are bound to earn more money than their costs of production. In the 19th century investment calculation was first developed by foresters to account for the fact that forestry production necessarily depends on the natural environment which, in financial terms, requires a long-term investment. However, discussions on the ‘soil rent theory’ and efforts to maximize profits from forestry production turned out to be a complete failure. We ask what can we learn from the history of forestry; that in the real world development, society and economics can only be shaped within the limits of nature, technology and human behaviour. Financial thinking may influence the status of the economy, and cannot be changed by intelligent technology, but financial interests shouldn’t govern economic thinking to the exclusion of all else. The latest financial crash and its consequences have demonstrated the dangers of the monetarian ideology, and consequently, we believe that a new concept of new sustainable economic orderis needed, in which nature, labour, and technology must be considered as production factors of equal weight. Currently, there is an over-emphasis on ‘capital’ which has traditionally been considered as a production factor in economics, and is weighted to favour monetary interest. However, the politically declared aim of economics in democracy is human interest, and the conservation of nature or ecological interest is required for sustainable production. What is meant by ‘financial times’? That business leaders as well as politicians generally overvalue the monetary component of the economy, which in consequence skews their view on reality, society and ecology. Banking must support highly specialized production and markets for the exchange of goods. So called financial industries offer ephemeral ‘product’, which are not goods nor services but just ‘money-making’. Their profits and exorbitant wages are depriving working people of revenue and technological resources. Solutions to the problems of forest economics are to be found outside forestry and contemporary forest policies. The concepts are available that could improve the system, and two of them will be outlined here, although currently there is little evidence that they are likely to be adopted in the present European political system. Nevertheless, sustainable development has been an official policy of the United Nations Conference on Environment and Develeopment (UNCD) since 1992, and we should continue to discuss and promote it.